A study on consumer awareness and perception of consumer deposit products offer by bank islam Cawangan Kulas/ Syed Mohd Halmi Wan Ismail Edruce - Wan Ismail Edruce, Syed Mohd Halmi (2007)
The objective of this study is to identify the awareness level on consumer on Consumer Deposit Product of Bank Islam by using 17 general questions, and 5 variables of positioning by modifying “A Customer-Based Brand Equity Framework” by Kevin Lane Keller( 1993) and "The Brand Awareness Pyramid” by David A. Aaker (1991). Besides the awareness level, this study also will examine on the perception of consumer towards the Consumer Deposit Product of Bank Islam by using the modified SERQUAL model by Parasuraman (1998) & Valarie A. Zeithaml (1988). The third objective is to identify the preferred media channel to deliver information of the Consumer Deposit Product.